Pericyte-like spreading by disseminated cancer cells activates YAP and MRTF for metastatic colonization - Er, Ekrem Emrah; Valiente, Manuel; Ganesh, Karuna; Zou, Yilong; Agrawal, Saloni; Hu, Jing; Griscom, Bailey; Rosenblum, Marc; Boire, Adrienne; Brogi, Edi; Giancotti, Filippo G.; Schachner, Melitta; et al. (Nature cell biology, 2018)
Metastatic seeding by disseminated cancer cells principally occurs in perivascular niches. Here, we show that mechanotransduction signalling triggered by the pericyte-like spreading of disseminated cancer cells on host tissue capillaries is critical for metastatic colonization. Disseminated cancer cells employ L1CAM (cell adhesion molecule L1) to spread on capillaries and activate the mechanotransduction effectors YAP (Yes-associated protein) and MRTF (myocardin-related transcription factor). This spreading is robust enough to displace resident pericytes, which also use L1CAM for perivascular spreading. L1CAM activates YAP by engaging β 1 integrin and ILK (integrin-linked kinase). L1CAM and YAP signalling enables the outgrowth of metastasis-initiating cells both immediately following their infiltration of target organs and after they exit from a period of latency. Our results identify an important step in the initiation of metastatic colonization, define its molecular constituents and provide an explanation for the widespread association of L1CAM with metastatic relapse in the clinic. Massagué and colleagues show that disseminated cancer cells use L1CAM to spread on capillaries and to achieve their outgrowth through activating YAP signalling.